Antifungal activity, antibiofilm, synergism and molecular docking of Allium sativum essential oil against clinical isolates of C. albicans - Pereira, Rafael (2021)
The aim of the present study was to investigate the biological activity of A. sativum essential oil against clinical isolates of C. albicans and, in addition, a computational study of the action of two main compounds of the essential oil on the protein of the fungus CYP51 was carried out. The Minimum Inhibitory Concentration and the Minimum Fungicidal Concentration were determined by the broth microdilution method. The biofilm formation was evaluated by biomass quantification using the violet crystal staining method. For the study of molecular docking computer simulations of interaction between CYP51 and ligands were performed using the AutoDock Vina code. The main constituents were diallyl disulfide, followed by diallyl disulfide. The essential oil demonstrated activity against clinical isolates of C. albicans. The essential oil showed a reduction progressive increase in the biomass produced from the biofilms of all yeasts tested in this study. The ligands Diallyl disulfide, Diallyl trisulfide and fluconazole formed complexes with the protein target.  Based on the results, the essential oil of A. sativum can be considered promising product for the development of new drugs in the prevention of infections associated with C. albicans. This study characterizes the effects of A. sativum essential oil against clinical isolates of C. albicans responsible for the development of pathologies in humans.